2017
DOI: 10.1007/978-3-319-55330-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Handling in Physiology and Disease

Abstract: Calcium (Ca) accumulation inside mitochondria represents a pleiotropic signal controlling a wide range of cellular functions, including key metabolic pathways and life/death decisions. This phenomenon has been first described in the 1960s, but the identity of the molecules controlling this process remained a mystery until just few years ago, when both mitochondrial Ca uptake and release systems were genetically dissected. This finally opened the possibility to develop genetic models to directly test the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 146 publications
3
48
0
Order By: Relevance
“…Calcium is a key modulator in a range of immunological, metabolic and developmental functions [199][200][201][202]. Calcium signalling is linked to a wide range of physiological and pathological processes [203][204][205], is a key driver for post-translational deimination [206][207][208] and plays an important role in the regulation of EVs [11,48]. In cattle, calcium is linked to many immunological pathways including inflammatory diseases [209], virus replication [210], parasitic infection [211], wound healing [212], reproduction [213,214] and adrenal function [215].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is a key modulator in a range of immunological, metabolic and developmental functions [199][200][201][202]. Calcium signalling is linked to a wide range of physiological and pathological processes [203][204][205], is a key driver for post-translational deimination [206][207][208] and plays an important role in the regulation of EVs [11,48]. In cattle, calcium is linked to many immunological pathways including inflammatory diseases [209], virus replication [210], parasitic infection [211], wound healing [212], reproduction [213,214] and adrenal function [215].…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of Ca 2+ into mitochondria has long been established as a key regulator of an array of cellular homeostatic processes as diverse as bioenergetics and cell death [1,2]. A series of seminal discoveries have recently elucidated the identity of the components that make up the mitochondrial Ca 2+ uniporter complex.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ binding to the lipid headgroup region severely alters properties of anionic bilayers (48). More relevant to mitochondrial membranes, Ca 2+ interacts strongly with CL, altering bilayer properties (e.g., demixing, phase behavior, and headgroup conformation) (19); Ca 2+ can disrupt protein-lipid interactions, causing effects such as respiratory complex disintegration (54); and mitochondrial Ca 2+ dyshomeostasis underpins a wide variety of mitochondrial diseases (55). In this study, we have directly shown that the binding of SS peptides reduces the effects of Ca 2+ on mitochondrial surface electrostatics ( Fig.…”
Section: Discussionmentioning
confidence: 99%